UPAYA MELAKSANAKAN EDUKASI KEPADA MASYARAKAT TENTANG PENTINGNYA KESEHATAN MENTAL MASA PANDEMI COVID-19 - Puspita Puji Rahayu,; Priscilla Titis Indiarti, (JURNAL PENGABDIAN MANDIRI, 2022)
One form of the Tridhama of Higher Education is the implementation of community service activities. National University of Karangturi as one of the institutions of higher education, seeks to help prepare the community to face the new normal by trying to share information and knowledge from the psychological aspect. Mental health affects how a person thinks, feels, acts, and makes decisions, as well as how a person handles stress and interacts with people so it is very important to have a healthy mentality. In order to interact and do activities well in society and avoid mental illness, it is important to always maintain mental health, this is the goal to be achieved through this activity. The benefits for participants are helping determine how to manage stress, relate to other people and be able to love yourself so that you are mentally healthy. Based on the results of the evaluation of the activities, it can be concluded that the online seminar activities received a good and positive assessment from the participants, so they want other seminar activities that are sustainable.